PERAN PUBLIK RELATIONS DALAM ISU DAN KRISIS PT. PERTAMINA (PERSERO) - Diah Widiargun; Prisca Dwi Puspa K; Eka Wulandari; Abdul Rafi J; Isniyunisyafna Diah Delima (Interpretasi: Communication & Public Relations, 2023)
Abstract Crises that hit a company always come unplanned. Therefore a company must have competent public relations practitioners. Which if there is a crisis the company will be ready to handle and resolve it as well as crisis prevention measures for the company. In this study, the authors used qualitative research methods with descriptive research types. This type of descriptive research is research that uses methods by describing a result of the research. The aim is to provide an explanation, and validation of the phenomena that occur in the field. To overcome a crisis and issue that must be done by a PR in a company is to introduce and validate a penetration in the design and practice of corporate management with the aim to at least manage corporate public issues as well or even better than the traditional management of operations that only think about profit. just. Issues management is applied both opportunistically and offensively, evolving from being a reactive crisis prevention tool to maintaining a strategic management discipline. Attention from stakeholders and other interested public- advocacy organizations, non-governmental organizations, government departments and agencies, news media and opinion leaders is bringing these issues onto the public agenda. Issues management strategies and tactics have long been tools of organized labour, governments and even activists, not just corporations. Keywords: Public Relations, Issues, Crisis, PT. Pertamina